Comparative Study of Biodiesel Production from Palm Oil and Waste Cooking Oil Using Two-Steps Transesterification - Yaacob, Marwan (2011)
Biodiesel is a renewable source of fuel which is seen to have the potential to substitute petroleum based diesel. In this study, a two step transesterification method was utilised for the production of biodiesel with different oil to alcohol ratio and potassium hydroxide (KOH) as a catalyst. The product was washed with 10% wt of warm distilled water (50°C) for several times before undergoing drying process with anhydrous sodium sulphate (Na2SO4). Biodiesel produced was analysed for water content and acid value. The result obtained will serve as basis of experimental procedures for the future work.